Estudo de biomonitoração para urânio e tório aplicado a análise por ativação neutrônica no Centro de Desenvolvimento da Tecnologia Nuclear - Rodrigo Reis de Moura (2019)
The study of environmental conditions using biological systems to quantify elements, whether metals, radionuclides or another type of agent (contaminant, pollutant, stressor) present in the environment using a living organism (biomonitor), is a strategy that uses the narrow relationship between the biomonitor and the environment studied, because the biomonitor can be part of the environment and interact with the agents present in it. Thus, biomonitoring should be able to quantify the stress magnitude, characterize the habitat as to the exposure degree to the stressor or the ecological response degree to exposure. Due to their high sensitivity characteristics, plants have been used as biomonitors in environmental impact studies and in various environmental monitoring programs. Most of the elements uptake in the environment by plants is through their roots. However, this uptake may also occur in contact with the atmosphere through some edible organs or shoot (leaves and stem). In addition, plants also have the ability to translocate and accumulate many of these elements in different parts of their anatomy. The Nuclear Technology Development Centre (CDTN/CNEN), located in Belo Horizonte, Minas Gerais, at the Campus of Federal University from Minas Gerais (UFMG) is an autarchy with the purpose of research and development, teaching and provision of services whose activities involve the handling and radioisotope production, has implemented in its organizational structure an Environmental Monitoring Program (PMA) since 1985 – being Licensed to operate by CNEN (National Nuclear Energy Commission) and IBAMA (Brazilian Institute of Environment and Renewable Natural Resources), LO 225/2012. Aiming at optimizing the environmental monitoring methodology developed by PMA/CDTN, this study was proposed in three stages: the first step, verification of the methodology of natural radioactivity analysis developed at PMA/CDTN; The second stage consisted of verifying the absorption, translocation and accumulation capacity of plants used in PMA/CDTN in a controlled environment. and the third stage consisted of establishing a natural biomonitor for the monitoring of the CDTN area. Epipremnum pinatum, is an abundant plant in the area of the CDTN, was evaluated and established, among the other species used in this study, as a biomonitor for presenting the main characteristics expected for such function. The analyzes for obtaining the mass fractions and the activity concentrations of both the plants and the soil hosting them were performed by the nuclear technique, Neutron Activation Analysis (k0-Method): Step 1, it was found that soil and plant sampling methodologies in PMA / CDTN can be optimized. Step 2, it was found that the species used in PMA/CDTN in greenhouse studies had good results only in the study in soil with naturally U and Th high concentrations. Step 3, it was verified that Epipremnum pinatum showed good uptake U and Th and low translocation to shoot in relation to their high accumulation in the roots. Thorium was more bioavailable in the outdoor study. Uranium was more bioavailable in the greenhouse study.